How Many Household Formation Systems Were There in Historic Europe? A View Across 256 Regions Using Partitioning Clustering Methods. - Szołtysek, Mikołaj; Ogórek, Bartosz (Historical Methods)
This paper reconsiders one of historical demography's most pertinent research problems: the fiddly concept of historical household formation systems. Using a massive repository of historical census micro-data from the North Atlantic Population Project and the Mosaic project, the four markers of Hajnal's household formation rules were operationalized for 256 regional rural populations from Catalonia in the west to central Siberia in the east, between 1700 and 1926. We then analyze these data using the Partitioning Around Medoids algorithm in order to empirically derive the "natural groups" based on the similarity and the dissimilarity of their household formation traits. Although regional differences between European household formation systems are readily identifiable, the two statistically most valid clustering solutions (k = 2; k = 4) provide a more complex picture of household formation regimes than Hajnal and his followers have been able to compile. Our finding that when regional populations cluster on similar household formation characteristics, they often come from both sides of Hajnal's "imaginary line," calls into question strict bipolar divisions of the continent. By and large, we show that the long-lived idea of two household formation systems in preindustrial Europe obscures considerable variability in historical family behavior, and therefore needs to be amended.